2016
DOI: 10.1002/iub.1486
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive functions of long-chain acyl-CoA synthetase 4 in gastric cancer

Abstract: Long chain acyl CoA synthetase 4 (ACSL4) is a key enzyme in fatty acid metabolism with marked preference for arachidonic acid (AA). Recent reports have implicated its crucial roles in tumorigenesis. However in gastric cancer (GC), the expression and function of ACSL4 remain unclear. In the present study, we identified ACSL4 as a potential tumor suppressor in GC. The ACSL4 expression in GC samples was evaluated by realtime PCR and immunohistochemistry. The results indicated that the mRNA and protein levels of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…In general, these findings were in line with the observations that ACSLs are upregulated in cancer. However, in a few exceptions, knockdown of ACSL1 or ACSL4 with specific small interfering RNA promoted lung (37) or gastric (25) cancer cell growth, respectively, and in vivo xenograft growth of gastric tumors (25).…”
Section: Effects Of Acsls On Carcinogenesis and Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these findings were in line with the observations that ACSLs are upregulated in cancer. However, in a few exceptions, knockdown of ACSL1 or ACSL4 with specific small interfering RNA promoted lung (37) or gastric (25) cancer cell growth, respectively, and in vivo xenograft growth of gastric tumors (25).…”
Section: Effects Of Acsls On Carcinogenesis and Cancer Developmentmentioning
confidence: 99%
“…Like those of ACSL1, the majority of studies of ACLS4 favor an oncogenic role. ACSL4 has been shown to be overexpressed in multiple cancer types, including colon (11,19), breast (20), liver (21-23) and prostate (24) cancer, while another study has shown its downregulation in gastric cancer (25). In terms of patient survival outcome, ACSL4 overexpression predicted poorer patient survival in stage II colon cancer [together with upregulated stearoyl-CoA desaturase (SCD)] (12) and in liver cancer (together with downregulated growth arrest and DNA damage inducible β) (21).…”
Section: Deregulated Expression Of Acsls In Clinical Cancermentioning
confidence: 99%
“…Particularly so since ACSL4 is required for ferroptosis which has a potential tumour-suppressive function. As an example, ACSL4 is significantly down-regulated in gastric cancer compared with cancer-adjacent normal gastric mucosa [36]. Moreover, transient overexpression of recombinant ACSL4 in gastric cancer cell lines significantly inhibited cell growth, proliferation and migration in vitro, whereas knockdown of ACSL4 induced reciprocal effects [36].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-ACSL3 rabbit polyclonal IgG antiserum (catalogue# PA5-42883) was purchased from Thermo Fisher Scientific, U.K.; its specificity has been validated in short hairpin RNAi knockdown experiments [37]. Anti-ACSL4 rabbit polyclonal IgG antiserum (catalogue# 22401-1-AP) was obtained from Proteintech Europe (Manchester, U.K.), its antigen specificity has been validated by both recombinant overexpression and siRNAi studies [36], and it has been used previously for detecting ACSL4 overexpression in HCC [57]. Liver tissue microarrays (#LV2091) were purchased from US Biomax (Rockville, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation